Spontaneous ssDNA stretching on graphene and hexagonal boron nitride in plane heterostructures - Binquan Luan (Nature Portfolio, 2019)
Single stranded DNA analysis is of interest for a range of applications; however, natural folding of DNA can cause problems with this. Here, the authors report on the in silico analysis of graphene and hexagonal-boron-nitride structures for the stretching and unfolding of DNA to allow for analysis.